Trends and Innovations in Health Behavior Change Interventions - Tarkhan, Alireza; Shabani, Ebrahim (Health Nexus, 2023)
This review article provides a comprehensive examination of the evolving landscape of health behavior change interventions from 2000 to 2023. It synthesizes key trends, innovations, and theoretical advancements in the field, highlighting the shift towards technology-enabled interventions and personalized approaches. The methodology involved a systematic literature search across major databases, focusing on peer-reviewed articles and systematic reviews that met specific inclusion criteria. The review identifies significant developments in digital health interventions, such as the use of mobile health applications, wearables, and artificial intelligence, and discusses how these technologies integrate with traditional behavior change theories. It also explores interdisciplinary approaches combining psychology, technology, and medicine, offering insights into their effectiveness and challenges. The article further addresses the barriers to implementation, ethical considerations, and the future trajectory of health behavior change interventions, emphasizing the need for scalable, evidence-based strategies. This review aims to inform practitioners, policymakers, and researchers about the current state and future potential of interventions in health behavior modification, underlining the importance of innovation in public health strategies.